Village Development Planning in The Digital Era: The Role and Interest of Stakeholders in Kotaagung, Tanggamus Regency - Yulianto Yulianto; Selvi Diana Meilinda; Ani Agus Puspawati; Anisa Utami (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2020)
This study aims to describe the planning process of village development in the digital era, focusing on the dynamics of stakeholder roles and interests. From descriptive qualitative research methods, village development planning in the digital era flows under the Ministry of Home Affairs Regulation No. 114/2014 and Law No. 6 of 2014. Furthermore, the dynamics of the planning process are more flexible with the role of media and technology sophistication. In the digital era, the village development planning process, especially in Kotaagung Sub-district villages, Tanggamus Regency, Lampung, is swift, which cuts bureaucracy and stagnated planning stages. Moreover, invitations to the village deliberations are conveyed in writing, a process that only fulfills administrative matters for archiving. Massive invitations are delivered through the devices of stakeholders deemed essential to be presented to determine development priorities. The dynamics of stakeholder and media are seen from the movement and correlation of roles, interests, and influences. That shows stakeholders are the main subject in village development planning in today's digital era. Therefore, the Village needs to respond to the changing times by planning and implementing the system with digitization in a systematic and applicable manner. Keywords: Development Planning; Village Development; Development Digitization